Defeating racism on African-Americans through music statements and achievements: An analysis of severals Kendrick Lamar’s album - Manik, Kosmas Merguna Ganda; Istiani, Imas (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This article examines how Kendrick Lamar’s music serves as a powerful confronting and defeating racism against African Americans through his lyrical statements and artistic achievements. Focusing on several of his seminal albums including Section.80, good kid, m.A.A.d city, To Pimp a Butterfly, and DAMN.—the analysis highlights Lamar’s incisive critique of systemic and institutionalized racism, police brutality, and cultural marginalization. His work not only exposes the structural inequalities faced by Black communities but also explores themes of identity, resilience, and empowerment, offering a nuanced portrayal of African-American life in contemporary America. By unpacking key songs and their socio-political contexts, this study reveals how Lamar’s music transcends entertainment to become a form of cultural resistance and social activism. Moreover, the article discusses the broader impact of Lamar’s achievements, including his role in shaping public discourse on race and inspiring collective empowerment within and beyond the African-American community. Ultimately, this analysis situates Kendrick Lamar as a pivotal figure whose artistic contributions significantly advance the struggle against racism through the transformative power of music.